Brain tissue oxygen dynamics while mimicking the functional deficiency of interneurons - Aksenov, Daniil P.; Doubovikov, Evan D.; Serdyukova, Natalya A.; Gascoigne, David A.; Linsenmeier, Robert A.; Drobyshevsky, Alexander (Frontiers in Cellular Neuroscience, 2022)
The dynamic interaction between excitatory and inhibitory activity in the brain is known as excitatory-inhibitory balance (EIB). A significant shift in EIB toward excitation has been observed in numerous pathological states and diseases, such as autism or epilepsy, where interneurons may be dysfunctional. The consequences of this on neurovascular interactions remains to be elucidated. Specifically, it is not known if there is an elevated metabolic consumption of oxygen due to increased excitatory activity. To investigate this, we administered microinjections of picrotoxin, a gamma aminobutyric acid (GABA) antagonist, to the rabbit cortex in the awake state to mimic the functional deficiency of GABAergic interneurons. This caused an observable shift in EIB toward excitation without the induction of seizures. We used chronically implanted electrodes to measure both neuronal activity and brain tissue oxygen concentrations (PO2) simultaneously and in the same location. Using a high-frequency recording rate for PO2, we were able to detect two important phenomena, (1) the shift in EIB led to a change in the power spectra of PO2 fluctuations, such that higher frequencies (8–15 cycles per minute) were suppressed and (2) there were brief periods (dips with a duration of less than 100 ms associated with neuronal bursts) when PO2 dropped below 10 mmHg, which we defined as the threshold for hypoxia. The dips were followed by an overshoot, which indicates either a rapid vascular response or decrease in oxygen consumption. Our results point to the essential role of interneurons in brain tissue oxygen regulation in the resting state.